Temporary Agency Work as a Means of Achieving Flexicurity? - Håkansson, Kristina; Isidorsson, Tommy; Kantelius, Hannes (Nordic Journal of Working Life Studies, 2012)
After decades of debate about flexibility, flexicurity has become a new buzzword in working life. Flexicurity refers to both the employer’s demand for flexibility and the employee’s demand for security. Thus, the idea is to solve the flexibility–security trade-off. There is also a discussion that mentions temporary agency work as one way of creating a flexicurity system. The flexibility potential is not called into question—numerical flexibility is a quite common motive for using temporary agency workers. However, the security dimension has to be scrutinized. The aim of this article is to analyze the temporary work agency industry’s potential for providing the security dimensions of the flexicurity model in a Swedish context. The study is based on a survey of whitecollar temporary agency workers in Sweden (n = 533). Overall, the vast majority do not perceive security. Our most important result is that both the work agency and the user firm have a dual impact on the agency workers’ perception of security.